Corporate real estate’s rising profile in the banking and finance industry - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2015)
Seven years after the financial crisis, profits have returned to the banking and finance industry – statistics compiled by the Federal Deposit Insurance Corporation (FDIC) for banks in the US showed that overall industry profits hit near record highs in 2014.